A New Rectangular Dielectric Waveguide Technique for Ripeness Determination of Palm Fruits - Mokhtar, Roslina (2004)
The thesis describes an investigation into the use of rectangular dielectric waveguide (RDWG) as a new technique for the determination of both complex permittivity and moisture content of oil palm fruits. The technique is analysed from the viewpoint of assessing its suitability as a simple, quick and flexible approach to permittivity and moisture measurements. An effective permittivity model is proposed where the rectangular dielectric waveguide/sample/rectangular dielectric waveguide interfaces are represented by a homogeneous medium with an effective permittivity obtained from the solution to the wave equation in the rectangular dielectric waveguide whilst the effective permittivity of the sample was found using a dielectric mixture model. The transmission and reflection coefficients are considered to be the effective values due to various interactions at the rectangular dielectric waveguide/sample/rectangular dielectric waveguide interfaces, which include both the radiation and guided modes. The measurement system consists of a HP8720B Vector Network Analyzer (VNA), rectangular dielectric waveguide, WR-90 standard waveguides and horn antennas. All microwave measurements were carried out using the VNA in the frequency range between 8 GHz and 12 GHz. A dielectric measurement software has been developed to control and retrieve data from the VNA using Agilent Visual Engineering Environment Software. The actual moisture content was found by applying standard oven drying method. A calibration equation relating the measured return loss and actual moisture content was established. The sensitivity of the rectangular dielectric waveguide sensor at 10 GHz is dB/% moisture content. The complex permittivity of the fruit samples was calculated using two methods. In the first method, the permittivity was calculated by inserting predicted moisture content values from an empirical relationship between the return loss and moisture content in the oil palm fruits into a dielectric mixture model. The second method directly calculates both the moisture content and permittivity using an optimization routine. The accuracy of the technique for the determination of moisture content was tested on 500 different fruit samples and was found to be within ±5% of the mean moisture content value from the standard oven drying method. The rectangular dielectric waveguide technique can be used to monitor fruit ripeness based on the measurement of the magnitude of the reflection coefficient alone. Fruit bunch with return loss values between 4.4 and 4.7 dB are considered ripe.